Genetic diversity characterization of maize populations using molecular markers - Torres-Morales, Braulio; Rocandio-Rodríguez, Mario; Santacruz-Varela, Amalio; Córdova-Téllez, Leobigildo; Coutiño Estrada, Bulmaro; López Sánchez, Higinio (Italian Journal of Agronomy, 2023)
Seventy-three maize populations were characterized to estimate the genetic distribution and structure of 8 maize races from the state of Chiapas, in addition to a population of the Balsas race of teosinte (Zea mays ssp. parviglumis Iltis & Doebley). A total of 31 microsatellite loci were evaluated in 25 individuals from each population, estimating their genetic diversity and Wright F statistics. The populations were grouped based on principal component and cluster analyses. A total of 787 alleles were counted, with an average of 25.4 alleles per locus and 91.8% polymorphic loci. Likewise, in the studied populations, 294 exclusive alleles were detected with low frequency, representing 37% of the total alleles. The populations from Zapalote Grande and Tepecintle races were the most differentiated, forming separate, better-defined groups, while the populations from Comiteco, Otolón, and Negro de Chimaltenango races tended to group, showing a relatively scattered allocation within the races. The FST statistic (differentiation index) was 0.197, indicating that 80.3% of the genetic variation was found among individuals within the accessions, which suggests that, under the current status of Chiapas maize populations, it would be more efficient to apply intra-population recurrent selection than hybridization breeding approaches.